MANAJEMEN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER PESERTADIDIK KELAS VII DI DI MA ZAMAIS ADILUWIH KECAMATAN ADILUWIH KABUPATEN PRINGSEWU - Toto Budiarto,; cipto handoko,; nur widi astuti, (UNISAN JURNAL, 2024)
Education is guidance or help given by adults to the development of children to reach maturity with the aim that children are capable enough to carry out their own life tasks without the help of others. Education for mankind is a very absolute need that must be met throughout life.Based on the above, the authors take the formulation of the problem in this study, namely "How is the Role of Islamic Religious Education Teachers in Shaping the Character of Students in Class VII MA ZAMAIS Adiluwih Kecamatan Adiluwih Kabupaten Pringsewu Tahun Pelajaran 2023/2024". The purpose of this study was to analyze the role of Islamic religious education teachers in shaping the character of students in class VII MA ZAMAIS Adiluwih Kecamatan Adiluwih Kabupaten Pringsewu . The results of the study found that Islamic religious education teachers have played a role in shaping the character of students, but their success has not been maximized because there are several inhibiting factors in the implementation of character building of students that influence it. Because the success of forming the character of students is not solely from the teacher factor but also influences, among others, the role of parents, the influence of the environment and the most important thing is the internal factor of the students, namely the motivation of the students themselves.